Consumo consciente e percepção do consumidor sobre ações corporativas vinculadas ao conceito de responsabilidade social: um estudo no setor da saúde - Todero, Mirele (My University, 2014)
The sustentable consumption is one of the main displays of a citizen social responsibility, being this one of the necessary dimensions for the sustentable local development. The ongoing study, from descriptive nature, aims to measure the reaction relative to the consciousness consumption and the perception of the company social responsibility, having as study subject the cooperative of the Health Service Unimed Nordeste RS. The quantitative research was carried out in the city of Caxias do Sul, Brazil, having as sample the local clients from Unimed. Descriptive statistics were used, Fatorial Analysis and Varience Analysis. The results point out that the respondents don´t practice the consciouness consumption yet. However, they attribute significative importance level to the practices related to it and also to the social responsibility. The factors of the Responsible Social Behavior of the Consumer, from the cooperative, the variance of these with the profile and the respondents characteristics were identified. The analysis of the researches discoveries takes into consideration the sociocultural aspects of the studied area and this way, looks for building relations among the concepts.
O consumo sustentável é uma das principais manifestações de responsabilidade social do cidadão, visto ser este uma das dimensões necessárias para o desenvolvimento local sustentável. O presente estudo, de natureza descritiva, propõe-se a mensurar os comportamentos relativos ao consumo consciente e a percepção de responsabilidade social empresarial, tendo como objeto para estudo a cooperativa de serviços de saúde Unimed Nordeste RS. A pesquisa quantitativa foi realizada na cidade de Caxias do Sul, Brasil, tendo como amostra os clientes locais da Unimed. Foram utilizadas estatísticas descritivas, análise fatorial e análise de variância. Os resultados apontam que os respondentes ainda não praticam o consumo consciente. Contudo, atribuem significativo grau de importância às práticas relacionadas a este e à responsabilidade social. Foram identificados os fatores de Comportamento Socialmente Responsável do Consumidor (CSRC) da cooperativa e a variância destes com o perfil e características dos respondentes. A análise das descobertas da pesquisa leva em conta os aspectos socioculturais da região em estudo e procura, assim, construir relações entre os conceitos.
Keywords: Administração; Responsabilidade social; Consumo consciente; Serviços de saúde; Unimed Nordeste-RS; Social responsibility; Consciousness consumption; Health service